How do small firms from European rural regions learn and innovate? - Cesário, M. (2012)
Contrarily to big firms, small firms interact intensively with the territory in which they located, as a signal of their embeddedness. The particular tight links they develop with their external environment reduce uncertainty risks. In general, for them, geographical and sociological proximities constitute the main sources of assets and information determining their perspectives and strategic choices. The present study uses a set of enquires, developed within the framework of a European research project, with the purpose of modelling the determinants of innovation in a bi-univocal relationship of interdependencies between small firms and their environmental contexts. We dealt mainly with lagging regions and a panel of 323 firms from the agro-food sector, located in 11 different European rural regions from six different countries. Using a set of variables able to characterise the innovative processes and through the application of k-mean clusters statistical analysis, it was possible to detect behavioural patterns towards innovation among those firms. Non-innovators, pioneer innovators and follower innovators were the identified patterns. Using cross tabs analysis between those patterns and a set of attributes dealing with the importance of human capital, the profile of each group were drawn.